Ultimate book of the future : incredible, ingenious, and totally real tech that will change life as you know it - Drimmer, Stephanie Warren (Washington, D.C. : National Geographic, 2022)
"Take a peek into how we might live in the future-how we'll get around, what we'll wear, and what kind of world we'll live in"--
Ages 8-12
Grades 4-6
Keywords: Forecasting -- Juvenile literature; Technological forecasting -- Juvenile literature; Inventions -- Juvenile literature